2022
DOI: 10.1038/s41419-022-05304-8
|View full text |Cite|
|
Sign up to set email alerts
|

HIF-α activation by the prolyl hydroxylase inhibitor roxadustat suppresses chemoresistant glioblastoma growth by inducing ferroptosis

Abstract: Patients with glioblastoma (GBM) have poor prognosis and limited treatment options, largely due to therapy resistance upon the induction of apoptosis. Ferroptosis emerges as a potential antineoplastic strategy to bypass apoptosis resistance in traditional therapeutics. Hypoxia is a fundamental hallmark of GBM and hypoxia-inducible factor (HIF) is the main regulator of hypoxia response, however, the role of HIF has not been sufficiently explored in GBM. Herein, we first discovered that amplifying HIF signals by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…In renal clear-cell carcinomas, HIF-2α activates HILPDA , which selectively enriches PUFA to promote lipid peroxidation and GPX4 inhibitor (RSL3, ML210, or ML162)-induced ferroptosis [ 61 ]. In glioblastoma (GBM), HIF-2α induced by the prolyl hydroxylase (PHD) inhibitor roxadustat, upregulated ferroptosis regulatory genes such as ACSL4 , PTGS2 , and CHAC1 , to enhance lipid peroxidation and erastin-induced ferroptosis, leading to the suppression of GBM cell growth in vitro and in vivo [ 118 ]. Another report showed that HIF-2α upregulated genes involved in lipid and iron metabolism in both colorectal cancer (CRC) cells and colon tumors in mice, which result in the cells being susceptible to ferroptosis induced by dimethyl fumarate [ 119 ].…”
Section: The Mechanism and Regulation Of Ferroptosis Modulated By Hyp...mentioning
confidence: 99%
“…In renal clear-cell carcinomas, HIF-2α activates HILPDA , which selectively enriches PUFA to promote lipid peroxidation and GPX4 inhibitor (RSL3, ML210, or ML162)-induced ferroptosis [ 61 ]. In glioblastoma (GBM), HIF-2α induced by the prolyl hydroxylase (PHD) inhibitor roxadustat, upregulated ferroptosis regulatory genes such as ACSL4 , PTGS2 , and CHAC1 , to enhance lipid peroxidation and erastin-induced ferroptosis, leading to the suppression of GBM cell growth in vitro and in vivo [ 118 ]. Another report showed that HIF-2α upregulated genes involved in lipid and iron metabolism in both colorectal cancer (CRC) cells and colon tumors in mice, which result in the cells being susceptible to ferroptosis induced by dimethyl fumarate [ 119 ].…”
Section: The Mechanism and Regulation Of Ferroptosis Modulated By Hyp...mentioning
confidence: 99%
“…Hypoxia is chronic in most tumors, and this condition is often exploited by cancer cells to sustain proliferation, metabolism, tumor invasion, and metastasis ( Yang et al, 2020 ). In this context, a key role is played by HIF1, a transcription factor activated by low oxygen and frequently overexpressed in cancer ( Su et al, 2022 ). Interestingly, HIF1 inhibits ferroptosis by: i) upregulating SCD1 to increase MUFA synthesis; ii) inhibiting the expression of ACSL4 to reduce Lipid-ROS generation, and iii) inhibiting the degradation of SLC7A11 ( Su et al, 2022 ).…”
Section: P53 and Stress Conditions Triggering Ferroptosismentioning
confidence: 99%
“…In this context, a key role is played by HIF1, a transcription factor activated by low oxygen and frequently overexpressed in cancer ( Su et al, 2022 ). Interestingly, HIF1 inhibits ferroptosis by: i) upregulating SCD1 to increase MUFA synthesis; ii) inhibiting the expression of ACSL4 to reduce Lipid-ROS generation, and iii) inhibiting the degradation of SLC7A11 ( Su et al, 2022 ). Therefore, the reduced efficacy of radiation or drug-based therapies in solid tumors has been, at least in part, associated with HIF1-mediated inhibition of ferroptosis ( Wang et al, 2019 ; Su et al, 2022 ).…”
Section: P53 and Stress Conditions Triggering Ferroptosismentioning
confidence: 99%
“…In GBM, RSL3 was reported to drive ferroptosis by targeting GPX4 expression [ 7 ]. Su et al showed that roxadustat can induce ferroptosis in chemoresistant GBM cells [ 8 ]. GBM is highly aggressive, and epithelial–mesenchymal transition (EMT) processes are thought to play a crucial role in the spread and metastasis of GBM [ 9 ].…”
Section: Introductionmentioning
confidence: 99%